Does Digital Readiness Matter? The Mediating Role of Digital Readiness Between Organizational Culture and Innovative Work Behavior Among SMEs in Indonesia - Azzahra, Fadia; Salendu, Alice; Sengkananingrum, Aisha Nuraini (Indonesian Journal of Business and Entrepreneurship, 2025)
Background: Innovation in Small and Medium Enterprises (SMEs) in Indonesia is essential for business development, requiring SMEs to foster innovative work behavior. However, some Indonesian SMEs still struggle to implement innovative work behavior, especially in utilizing digital technology for innovation in this digital era.Purpose: This study aims to explore the role of digital readiness in mediating organizational culture’s impact on the innovative work behavior of SME employees in Indonesia. Design/methodology/approach: The research employed a quantitative approach using Structural Equation Modeling - Partial Least Squares (SEM-PLS) analysis. The survey was distributed to SME employees in Indonesia. This research used 185 respondents for further data analyzing.Findings/results: The results reveal that digital readiness only mediates the relationship between market culture and innovative work behavior. On the other hand, digital readiness does not mediate adhocracy and clan culture to innovative work behavior. Conclusion: Results interestingly suggest that digital readiness significantly mediates market culture to innovative work behavior. Adhocracy and clan cultures may directly instill innovative work behavior, as confirmed by previous studies.Originality/value (State of the art): This is the first study to investigate how types of culture are associated with innovative work behavior mediated by digital readiness. Keywords: Innovation, innovative work behavior, organizational culture, digital readiness, SME